Nano-functionalization and evaluation of antimicrobial activity of Tinospora cordifolia against the TolB protein of Pseudomonas aeruginosa – An antibacterial and computational study - Nath, Himporna; Khataniar, Ankita; Bania, Kusum K.; Mukerjee, Nobendu; Al-Hussain, Sami A.; Zaki, Magdi E. A.; Rajkhowa, Sanchaita (Frontiers in Microbiology, 2023)
Antibacterial drug resistance, brought on by the overuse of antibiotics, is one of the biggest threats to human health. It is crucial to consider cutting-edge strategies, such as herbal remedies, to control multidrug-resistant (MDR) bacteria. Therefore, this study evaluated the phytochemical, antioxidant and antibacterial properties of the various Tinospora cordifolia extracts. The plant was reported from the Charaideo district of Assam, whose methanolic stem extract showed the maximum activity towards the nosocomial pathogen Pseudomonas aeruginosa. Consequently, the active compound was isolated and characterized as belonging to the class Cordifoliside using NMR. Gold (Au) and silver (Ag) nanoparticles were used to functionalize the isolate. The functionalized isolates showed enhanced antimicrobial activity against P. aeruginosa compared to the unfunctionalized isolate. This study has also attempted to understand the interaction of the cordifoliside class with its target using in-silico methods. The most reactive compound from the Cordifolisides (norditerpene furan glycosides) was determined using Density Functional Theory (DFT) analysis. Our study revealed Cordifoliside C as the most reactive compound whose interactions with the TolB protein were studied using molecular docking methods, which revealed good binding interactions of Cordifoliside C with the TolB protein.